Optionality of Movement. (24th June 2020) - Titov, Elena
Abstract: This article looks at constructions involving optional movement of contrastive foci and argues that this type of reordering cannot be accounted for by assuming that it is driven by a syntactic feature. I maintain that an interface‐based approach that rests on the principles of economy fares better at capturing the data, as it accounts not only for optionality of contrastive‐focus movement, which is found in a wide variety of languages, but also for multiple landing sites for contrastive‐focus movement, which are found in scrambling languages, such as Russian.